The Effects of Seasonal Variation on the Outcomes of Patients Undergoing Off-Pump Coronary Artery Bypass Grafting - Ling Wu; Pei-shuang Lin; Yun-tai Yao (Reviews in Cardiovascular Medicine)
Background: The impact of seasonal patterns on the mortality and morbidity of surgical patients with cardiovascular diseases has gained increasing attention in recent years. However, whether this seasonal variation extends to cardiovascular surgery outcomes remains unknown. This study sought to evaluate the effects of seasonal variation on the short-term outcomes of patients undergoing off-pump coronary artery bypass grafting (OPCABG). Methods: This study identified all patients undergoing elective OPCABG at a single cardiovascular center between January 2020 and December 2020. Patients were divided into four groups according to the season of their surgery. The primary outcome was the composite incidence of mortality and morbidity during hospitalization. Secondary outcomes included chest tube drainage (CTD) within 24 h, total CTD, chest drainage duration, mechanical ventilation duration, and postoperative length of stay (LOS) in the intensive care unit (ICU) and hospital. Results: Winter and spring surgeries were associated with higher composite incidence of mortality and morbidities (26.8% and 18.0%) compared to summer (15.7%) and autumn (11.1%) surgeries (p < 0.05). Spring surgery had the highest median CTD within 24 hours after surgery (640 mL), whereas it also exhibited the lowest total CTD (730 mL) (p < 0.05). Chest drainage duration was longer in spring and summer than in autumn and winter (p < 0.05). While no significant differences were observed in mechanical ventilation duration and hospital stay among the four seasons, the LOS in the ICU was longer in summer than in autumn (88 h vs. 51 h, p < 0.05). Conclusions: The OPCABG outcomes might exhibit seasonal patterns in patients with coronary heart disease.